2009
DOI: 10.1177/0363546509341174
|View full text |Cite
|
Sign up to set email alerts
|

Medial Open Wedge High Tibial Osteotomy

Abstract: To prevent the unintentional increase of the posterior tibial slope, special attention should be paid to locate the intact cortical hinge on the lateral, not the posterolateral, side of the tibia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 21 publications
(23 reference statements)
1
45
0
2
Order By: Relevance
“…The opening gap angle and hinge position ratio in the sagittal view was correlated with an increased change in TPS. One study to 12 knees using cadavers [ 8 ] investigated whether the variable hinge position actually affected the change in TPS, and concluded that unintentional change in TPS could be avoided if a true lateral hinge position was achieved by performing a complete posterior osteotomy and inspecting the osteotomy using the gap ratio. They also stated that the osteotomy of the proximal tibia using the lateral location as a cortical hinge affected the change in TPS less than using the posterolateral location as a cortical hinge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The opening gap angle and hinge position ratio in the sagittal view was correlated with an increased change in TPS. One study to 12 knees using cadavers [ 8 ] investigated whether the variable hinge position actually affected the change in TPS, and concluded that unintentional change in TPS could be avoided if a true lateral hinge position was achieved by performing a complete posterior osteotomy and inspecting the osteotomy using the gap ratio. They also stated that the osteotomy of the proximal tibia using the lateral location as a cortical hinge affected the change in TPS less than using the posterolateral location as a cortical hinge.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have tried to investigate the relationship between the hinge position and the change in TPS after OWHTO, but have a small number of cases, which was one study to 12 knees using cadavers [ 8 ] and another to 19 knees using three-dimensional computed tomography (3DCT) [ 9 ]. They concluded that the hinge position affected the change in TPS, and a posterolateral hinge position led to an increase in TPS after OWHTO.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported several factors related to PTSA in medial opening wedge HTO, including the triangular shape of the proximal tibia, 4 , 10 , 19 insufficient posterior osteotomy or release of posterior soft tissue, 14 , 24 anterior plate placement, 2 , 10 , 21 , 22 , 24 and posterior hinge point. 17 , 24 However, the most important cause of increased PTSA is the presence of an asymmetrical gap opening in the sagittal plane, which may be affected by the direction of wedge insertion. Song et al 23 reported that the normal tibial posterior slope can be maintained if the anterior opening gap is approximately 67% of the posterior opening gap in navigation-assisted HTO; this is consistent with our result wherein the opening gap ratio (anterior opening gap/posterior opening gap) was 0.86 ± 0.11, with a mean increase in PTSA of 4°.…”
Section: Discussionmentioning
confidence: 99%
“…64 A study in human alcoholics showed an increase in glutamate–glutamine and GABA labeling in heavy compared with light drinkers. 64 In our study, we found many alcohol-metabolizing enzymes that were upregulated by alcohol consumption, in agreement with a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…64 A study in human alcoholics showed an increase in glutamate–glutamine and GABA labeling in heavy compared with light drinkers. 64 In our study, we found many alcohol-metabolizing enzymes that were upregulated by alcohol consumption, in agreement with a previous study. 65 Furthermore, alcohol-responsive glutamate and GABA mRNAs were detected in SNs (GABA-related mRNAs were associated with the upregulated alcohol-responsive mRNAs, see Table 5).…”
Section: Discussionmentioning
confidence: 99%